Application Of Earthquake Resistant Standards (SNI 1726: 2019) Against Building in Yogyakarta City (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
The load-bearing structure is made from a Special Moment Bearer Frame Structure. The structure is prepared against earthquake loads in line with the Indonesian National Standard 1726: 2019 (Earthquake Resistance Planning Standards for Building Structures), which is based on an earthquake plan with a return period of 2,500 years. The earthquake load study adopts the response spectrum approach based on the Earthquake Resistance Planning Procedure for Building and Non-Building Structures (Indonesian National Standard 1726: 2012 and Indonesian National Standard 1726: 2019). This study aims are to make a comparison between the two procedures in terms of changes in seismic bottom shear forces, and to examine the performance of the building structure in terms of the inter-level drift that occurs. The results of dynamic analysis obtained using the ETABS v.19.0.0 program showed an increase in seismic bottom shear force by 133%, both in the X direction and in the Y direction. The result directions also compared by using the 2012 Indonesian National Standard. Judging from the terms of deviation between levels, the building structure does not exceed the provisions, either according to the 2012 or 2019 Indonesian National Standard. The City Hall Tower building structure is still in a stable condition when the stability of the building and the P-Delta effect are checked in the subsequent control study.Keywords: - component; formatting; style; styling